The Caelicolae: a Judaizing Christian Sect that Emerged at the Time of Augustine of Hippo - González Salinero, Raúl (Henoch, 2022)
Despite the dearth of information provided by sources, we are aware of the existence of a Christian sect known as the Caelicolae (literally, “Heaven Worshippers”) in early-5th century North Africa. Their doctrine seems to have resulted from a synthesis or syncretism between Christian and Jewish tendencies and, even though their true nature remains shrouded in doubt, the two imperial laws through which Honorius decreed the ban on this cult (CTh, 16.5.43 and 16.8.19) point to its predominantly judaizing nature. Augustine claimed that the Caelicolae had seduced a great number of Christians into accepting their new and sacrilegious baptism. Furthermore, Aptus, the Judaizer mentioned by the bishop of Hippo in the epistle he sent to bishop Asellicus in 418 (Epist. 196) may have belonged to that very same group. According to Augustine’s account, this troublesome figure, whose followers referred to themselves as Jews and Israelites, taught Christians to judaize by observing Jewish dietary prescriptions and rituals.